Process Adapted Multiscale Material Characterization - Cholewa, Simon; Marschall, Maximilian; Schmidt, Michael; Drummer, Dietmar (Progress in Powder Based Additive Manufacturing, 2025)
Since the laser based powder bed fusion of polymers process involves previously unknown boundary conditions, process-adapted powder characterization at the particle and powder layer levels is essential. In this chapter, new measurement methods are presented, and the results are discussed within the context of process-adapted boundary conditions for powder flow behavior and optical and thermal propertie
Created from Fastlane, Scopus look-up